Preparation and anti-triple-negative breast cancer cell effect of a nanoparticle for the codelivery of paclitaxel and gemcitabine - Fan Yang; Zehui Fan; Lixia Zhang; Yanjuan He; Run Hu; Jinkun Xiang; Shiyang Fu; Guowei Wang; Jianlong Wang; Xiaojun Tao; Pan Zhang (Discover Nano, 2023)
Abstract Amphiphilic polymers (HA-ANI) were prepared by grafting hyaluronic acid (HA) and 6-(2-nitroimidazole)hexylamine (ANI) and then self-assemble in water to form nanoparticles (NPs) that could be loaded with paclitaxel (PTX) and gemcitabine (GEM) by dialysis. Infrared spectroscopy and 1H-NMR indicated the successful synthesis of HA-ANI. Three different ratios of NPs were prepared by adjusting the ratios of hydrophilic and hydrophobic materials, and the particle size decreased as the ratio of hydrophilic materials increased. When HA:ANI = 2.0:1, the nanoparticles had the smallest size distribution, good stability and near spherical shape and had high drug loading and encapsulation rates. In vitro release experiments revealed that NADPH could accelerate the drug release from NPs. Cellular uptake rate reached 86.50% at 6 h. The toxic effect of dual drug-loaded nanoparticles (P/G NPs) on MDA-MB-231 cells at 48 h was stronger than that of the free drug. The AO/EB double-staining assay revealed that a large number of late apoptotic cells appeared in the P/G NPs group, and the degree of cell damage was significantly stronger than that of the free drug group. In the cell migration assay, the 24 h-cell migration rate of the P/G NPs group was 5.99%, which was much lower than that of the free group (13.87% and 17.00%). In conclusion, MDA-MB-231 cells could effectively take up P/G NPs, while the introduction of the nano-codelivery system could significantly enhance the toxicity of the drug to MDA-MB-231 cells as well as the migration inhibition effect.